Utilization of Dairy Wastewater for Pollutants Removal and High Lipid Biomass Production by a Newly Isolated Microalgal Strains Chloromonas playfairii and Desmodesmus opoliensis - Guruvaiah, Mahendraperumal; Narra, Madhuri; Shah, Ekta; James, Jisha; Kurchania, Anil (International Journal of Applied Sciences and Biotechnology, 2015)
Two new unicellular microalgal species from milk processing unit situated at Anand, India were screened and tested for their growth rate and nutrient removal capability under dairy wastewater at outdoor conditions in a simple column aeration photobioreactor. Results of 18s rRNA sequence analysis indicated that these strains have a close relationship with Chloromonas playfairii and Desmodesmus opoliensis named as SBC 2 and SBC 3, respectively. Both the strains removed more than 92% of ammonical nitrogen and 99% of total phosphorus, whereas COD and BOD reductions were found to be more than 95%. Maximum biomass production was 1.7 and 1.2 g L-1 and lipid content was 15 and 12%, respectively from SBC 2 and SBC 3 after 15 d cultivation. This study demonstrates the potential of algae based biofuel production by coupling wastewater treatment with microalgae cultivation for high lipid containing biomass production using Chloromonas playfairii and Desmodesmus opoliensis. Int J Appl Sci Biotechnol, Vol 3(4): 699-707